Evaluation of varietal resistance and efficacy of botanical and chemical treatments against seedborne fungal pathogens in safflower (Carthamus tinctorius L.) - Kakar, Muhammad Ayaz; Wagan, Khadim Hussain; Qambrani, Rawal Ahmed; Khaskheli, Muhammad Ibrahim; Abro, Manzoor Ali; Ali, Muharam; Qambrani, Ramsha; Qambrani, Zareen; Khaskheli, Sajad Ali (Journal of Pure and Applied Agriculture, 2025)
Safflower (Carthamus tinctorius L.) is a valuable oilseed crop cultivated for its economic and nutritional benefits; however, its productivity is often compromised by seed-borne fungal infections. Despite growing interest in environmentally friendly plant protection strategies, limited research has addressed the comparative impact of multiple fungal pathogens on different safflower varieties and the integrated use of botanical and chemical control methods. This study aims to investigate the incidence and pathogenic effects of five seed-borne fungi Alternaria carthami, Aspergillus niger, Rhizopus sp., Curvularia sp., and Fusarium oxysporum isolated from four safflower varieties (S-208, Thori-78, SAF-130, and SAF-30), and to evaluate the efficacy of selected plant extracts and commercial fungicides in controlling fungal growth. Results revealed A. niger as the most prevalent pathogen, with isolation rates between 27.50% and 61.50%, followed by A. carthami (23.00%–40.00%). The Thori-78 variety showed the highest incidence of fungal contamination, while S-208 showed the lowest. Rhizopus sp. was not isolated from S-208. Infected seeds demonstrated significantly lower germination rates, with the healthiest germination observed in non-infected S-208 seeds. In vitro antifungal tests with plant extracts Aloe vera, toothbrush plant, garlic, neem, and giant milkweed showed garlic extract as the most effective at all tested concentrations (10%, 20%, 30%), followed by neem. Among five fungicides (Aliette, Topsin-M, Dithane M-45, Carbendazim and Acrobat), Dithane M-45, Carbendazim, and Topsin-M showed the highest antifungal activity, especially at higher doses, and promoted improved plant height and biomass. This study fills a key research gap by combining varietal susceptibility analysis with integrated fungal management strategies, highlighting the potential of both botanical and synthetic agents in safeguarding safflower crops and enhancing overall agricultural productivity.